A Comparative Content Analysis of Digital Channels for Ventricular Assist Device Patients, Caregivers, and Healthcare Practitioners. Issue 8 (November 2019) - Ko, Keum Hee Kimmi; Dunn, Jessica Lea; Straker, Karla; Nusem, Erez; Gregory, Shaun; Wrigley, Cara
Abstract : This article seeks to review and analyze the emergence of digital channels designed for ventricular assist device (VAD) patients, caregivers, and practitioners and to understand how such digital channels support the user experience of VAD implantation. Following a content analysis methodology, the authors investigated 16 digital channels designed for VAD patients, caregivers, and practitioners, with data being analyzed thematically. Competitor Positioning Matrix diagrams were created to visually represent the landscape of digital channels that support VAD stakeholders. These matrices identified opportunities and potential areas for improvement in future VAD digital channel design, with an emphasis on interactivity coupled with intelligence and focus along the various stages of the VAD patient journey. Innovation in digital channels has the potential to reduce burden on all users by enabling communication, self-management, and remote monitoring. Digital channels can be information enhanced for point of care, function as a decision support tools or be used to empower patient-caregiver pairs to be more sufficient with self-management, while enabling communication with their practitioner. Abstract : Supplemental Digital Content is available in the text.